The property issue. Politics of space and data. - (:unkn) unknown (ARCH+, 2020)
„Wem gehört der Boden?" ist eine zentrale Frage, denn der Raum ist eine ebenso lebensnotwendige Ressource wie Luft und Wasser. Doch für die Stadtplanung spielt das Eigentum an Daten heute eine ebenso wichtige Rolle wie die Frage nach dem Besitz von Grund und Boden. In der Publikation wird die Frage des Eigentums an Boden und an Daten von vielen Seiten beleuchtet.

Who owns the land? This question is of crucial importance for all societies and their coexistence. This is because the availability of land and property controls the production of space and the social order. The fact that land (space) is as vital to life as air and water means that its use should not succumb to the unmistakable play of free (market) forces and individual whims. Who owns data? For urban planning, the issue of data ownership has become just as relevant as land ownership. In this issue the authors therefore discuss the politics of space and the politics of data, the real and virtual capital of the city of the future. The debate is guided by two main questions: How do we deal with space and data as planning resources? And what role do architects and urban planners play in the digital society?
Keywords: Bodenpolitik; Bodenrecht; Grundeigentum; Planungsdaten; Regionale Daten; Datenmaterial; Eigentumsrecht; Raumpolitik; Raumplanungspolitik; Planungstheorie